Burnout Syndrome Prevention Measures among Nursing Staff: Implementing a Mobile Application based on MIT's App Inventor Tool using the Scratch Programming Code - Lafraxo, Mohammed Amine; Ouadoud, Mohammed; El Madhi, Youssef; Rehali, Mourad; Soulaymani, Abdelmajid (International Journal of Online and Biomedical Engineering, 2021)
This research study serves, on the one hand, to assess the prevalence of burnout among the nursing staff. On the other hand, to determine the socio-demographic and professional characteristics associated with burnout. The aim is to propose an interactive tool to cope with burnout. This is an observational study of a cross-sectional type, conducted among a population of 30 nurses over 4 months. A two sections self-administered survey was used to determine: 1) Sociodemographic and professional characteristics; 2) the Copenhagen Burnout Inventory to evaluate burnout. In total, 17% of nurses display a high level of burnout in both its dimensions and that more than 50% are highly susceptible to it. Moreover, 83% of participants agreed to use the technology as a solution. The proposed prevention solution to cope with burnout was developed by the scratch programming code using the app inventor tool, it consists of three online services (Training, Assessment, Support).